The influence of fine aggregate on the bituminous mixture mechanical behaviour - Pais, Jorge C. (2002)
This paper presents the results obtained during the implementation of a new laboratory tests to evaluate the asphalt-aggregate adhesion. Those tests performed on the mixture mastic, are based on tension and shearing properties of the mixture. The calibration and validation of those laboratory tests was made comparing the performance of mastic specimens with the fatigue and permanent deformation of corresponding mixtures. This paper presents the fatigue and permanent deformation results of bituminous mixtures used in wearing and base courses. For each type of mixture, five mixtures were defined, by changing the gradation curve (from more to less fine aggregates). All mixtures were produced and compacted in laboratory. Specimens for tests were obtained by cored and sawed from compacted slabs. For stiffness and fatigue, tests were executed on four point bending beam on controlled strain, whereas for permanent deformation tests were the repetitive simple shear test at constant height.